Effect of lanthanum content on the conduction behaviors and relaxation processes of lead lanthanum zirconate titanate antiferroelectric ceramics. Issue 10 (July 2020) - Liang, Xuewei; Zhang, Tianyuan; Zhao, Zhangyuan; Hu, Kangjia; Li, Shenhou; Hui, Wenchang; Zhang, Yong
Abstract: (Pb1-x Lax ) (Zr0.92 Ti0.08 )1-x/4 O3 (PLZT x /92/8, x  = 3, 5 and 7 at%) ceramics with compositions near the antiferroelectric (AFE)-ferroelectric (FE) phase boundary were fabricated by a solid-state reaction method. The effect of lanthanum content on the conduction behaviors and relaxation processes has been investigated. It was verified that the main phase with orthorhombic structure was formed in all compositions. The increase of lanthanum substitution resulted in an enhancement of diffuse phase transition. Impedance analysis suggested that the ac conductivity decreased with increasing lanthanum content. Moreover, thermally stimulated depolarization current study was utilized to establish the correlation between defect structures and relaxation processes. It showed three peaks with distinct characteristics, which originated from dipole orientation, oxygen vacancy migration and phase transition respectively. The oxygen vacancy-related defects induced by lanthanum doping were mainly responsible for the variation of conduction behaviors and relaxation processes.